Outcomes in Adult Sinonasal Rhabdomyosarcoma. (July 2017) - Stepan, Katelyn; Konuthula, Neeraja; Khan, Mohemmed; Parasher, Arjun; Del Signore, Anthony; Govindaraj, Satish; Genden, Eric; Iloreta, Alfred
Objective: To describe patient demographics, histology, treatment modalities, and survival associated with adult sinonasal rhabdomyosarcoma. Study Design: Retrospective review of a national database. Setting: Tertiary medical center. Subjects and Methods: Patient demographics, tumor histology, treatment modalities, and survival trends were examined for patients aged ≥18 years who were diagnosed with sinonasal rhabdomyosarcoma between 2004 and 2013 with the National Cancer Database. Kaplan-Meier analysis and the log-rank tests were performed to determine the unadjusted association between overall survival and various patient and disease characteristics. Results: A total of 186 patients were identified; 5-year overall survival was 28.4%. Over half of patients were between 18 and 35 years old at diagnosis (53.8%), which was associated with improved 5-year overall survival over patients >35 years old (31.9% vs 24.4%, P = .014). Alveolar sinonasal rhabdomyosarcoma was most common (66.7%). There was no statistical difference in 5-year overall survival between alveolar and embryonal subtypes (30.5% vs 41.6%, P > .05). Metastatic disease was present in 27.7% of patients and was associated with worse 5-year overall survival (14.7% vs 33.9%, P < .0001). The majority of patients were treated with chemotherapy with adjuvant radiation (49.5%). A quarter of patients were treated with surgery plus chemoradiation (25.8%). Conclusion: We present the largest analysis of adult sinonasal rhabdomyosarcoma using a standardized national based database. Adult sinonasal rhabdomyosarcoma has a very poor prognosis independent of histologic subtype. The small number of surgical cases limits the ability of the analysis to accurately compare treatment with chemoradiation with and without surgery.